Relationship between glycated albumin and glycated hemoglobin according to glucose tolerance status: A multicenter study. (May 2016) - Mo, Yifei; Ma, Xiaojing; Li, Hong; Ran, Xingwu; Yang, Wenying; Li, Qiang; Peng, Yongde; Li, Yanbing; Gao, Xin; Luan, Xiaojun; Wang, Weiqing; Xie, Yun; et al.
Highlights: GA is positively correlated with HbA1c ( r  = 0.832, P  < 0.001). 1% increase of the mean HbA1c is associated with a 2.84% increase in mean GA. For HbA1c of 6.5 and 7.0%, the calculated GA is 18. 3% and 19.7%. The GA/HbA1c ratio increases with the presence of glucose intolerance. Increased 30-min glucose and decreased BMI are related to GA/HbA1c ratio. Abstract: Aims: To determine the relationship between glycated albumin (GA) and glycated hemoglobin (HbA1c) and to explore the association of glycated albumin/glycated hemoglobin (GA/HbA1c) ratio with glucose indices in Chinese subjects with varying glucose tolerance status. Methods: This hospital-based, cross-sectional study involved 953 participants without known diabetes from 11 centers in China. Oral glucose tolerance test (OGTT) was used to identify three groups of subjects: normal glucose regulation ( n  = 194), impaired glucose regulation ( n  = 303) and newly diagnosed type 2 diabetes group ( n  = 456). The GA, HbA1c and GA/HbA1c ratio were tested. Results: GA was positively correlated with HbA1c ( r  = 0.832, P  < 0.001). After correcting for age, sex and BMI, the correlations remained significant ( r  = 0.824, P  < 0.001). Linear regression analysis estimated that a 1% increase of HbA1c was associated with a 2.84% increase of GA (GA = 2.843 × HbA1c − 0.203; R 2  = 0.692, P  < 0.001). GA would be 18.3 (16.7–19.9)% and 19.7 (18.0–21.4)% with HbA1c of 6.5% (48 mmol/mol) and 7.0% (53 mmol/mol). The mean GA/HbA1c ratio was 2.81 ± 0.38, and it significantly increased with the presence of glucose intolerance (all, P  < 0.05). In the total study population, GA/HbA1c was correlated with BMI, glucose levels and 30-min insulin during OGTT, the homeostatic model assessment of β-cell function (HOMA-β), and Δ I 30 /Δ G 30 (all, P  < 0.05). Increased glucose at 30 min (standardized β  = 0.221, P  < 0.001), and decreased BMI (standardized β  = −0.114, P  = 0.008) were associated with elevated GA/HbA1c ratio by multiple linear regression (adjusted R 2  = 0.045). Conclusions: The relationship between GA and HbA1c was strong. The GA/HbA1c ratio was related to acute postprandial glucose fluctuation and BMI level.